Molecular line emission in NGC 4945, imaged with ALMA - Henkel, Christian; Mühle, S.; Bendo, G.; Józsa, G. I. G.; Gong, Y.; Viti, S.; Aalto, S.; Combes, F.; García-Burillo, S.; Hunt, L. K.; Mangum, J.; Martín, S.; et al. (Astronomy and astrophysics, 2018)
NGC 4945 is one of the nearest (D ≈ 3.8 Mpc; 1″ ≈ 19 pc) starburst galaxies. To investigate the structure, dynamics, and composition of the dense nuclear gas of this galaxy, ALMA band 3 (λ ≈ 3−4 mm) observations were carried out with ≈2″ resolution. Three HCN and two HCO+ isotopologues, CS, C3H2, SiO, HCO, and CH3C2H were measured. Spectral line imaging demonstrates the presence of a rotating nuclear disk of projected size 10″ × 2″ reaching out to a galactocentric radius of r ≈ 100 pc with position angle PA = 45° ± 2°, inclination i = 75° ± 2° and an unresolved bright central core of size ≲2″. The continuum source, representing mostly free-free radiation from star forming regions, is more compact than the nuclear disk by a linear factor of two but shows the same position angle and is centered 0.′′39 ± 0.′′14 northeast of the nuclear accretion disk defined by H2O maser emission. Near the systemic velocity but outside the nuclear disk, both HCN J = 1 → 0 and CS J = 2 → 1 delineate molecular arms of length ≳15″ (≳285 pc) on opposite sides of the dynamical center. These are connected by a (deprojected) ≈ 0.6 kpc sized molecular bridge, likely a dense gaseous bar seen almost ends-on, shifting gas from the front and back side into the nuclear disk. Modeling this nuclear disk located farther inside (r ≲100 pc) with tilted rings provides a good fit by inferring a coplanar outflow reaching a characteristic deprojected velocity of ≈50 km s−1. All our molecular lines, with the notable exception of CH3 C2H, show significant absorption near the systemic velocity (≈571 km s−1), within the range ≈500-660 km s−1. Apparently, only molecular transitions with low critical H2 density (ncrit ≲ 104 cm−3) do not show absorption. The velocity field of the nuclear disk, derived from CH3 C2H, provides evidence for rigid rotation in the inner few arcseconds and a dynamical mass of Mtot = (2.1 ± 0.2) × 108 M⊙ inside a galactocentric radius of 2.′′45 (≈45 pc), with a significantly flattened rotation curve farther out. Velocity integrated line intensity maps with most pronounced absorption show molecular peak positions up to ≈1.′′5 (≈30 pc) southwest of the continuum peak, presumably due to absorption, which appears to be most severe slightly northeast of the nuclear maser disk. A nitrogen isotope ratio of 14N/15N ≈ 200-450 is estimated. This range of values is much higher then previously reported on a tentative basis. Therefore, because 15N is less abundant than expected, the question for strong 15N enrichment by massive star ejecta in starbursts still remains to be settled.
Published online 31 July 2018
Gesehen am 02.10.2019